Mitigasi Transmission Line Loss Melalui Perubahan Jarak Antar Konduktor - Wijaya, Yusuf Pandhu (TEKNO: Jurnal Teknologi Elektro dan Kejuruan, 2020)
Transmission Line Loss is an obstacle that cannot be avoided from the electricity transmission process. Transmission Line Loss is a phenomenon that is affected by loss of power due to corona and loss of power due to conductance resistance. Transmission Line Loss can be detrimental to the seller, because the electricity sent to the buyer is partially lost in the shipping process. However, losses can be reduced by increasing the distance between conductors so that the risk of Transmission Line Loss can be mitigated. In the transmission between the Waru bay Buduran substation, 83MW - 145MW of power is transmitted and 1.1 MW - 1.9 MW is lost due to losses in the transmission. Through this method, the loss of the transmission line can be reduced by 2.8% - 11.2%, so that the loss of the transmission line is reduced to 0.8MW – 1.8MW.